(untitled) (Eurasian Journal of Humanities and Social Sciences, 2024)
This article examines the relevance of the security problem in the Middle East region and how the processes taking place in the Middle East region are inextricably linked with neighboring countries. In addition, the benefits of the world’s leading countries from this region will be analyzed.